2015
DOI: 10.1097/sla.0000000000001078
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities in Perioperative Outcomes of Major Procedures

Abstract: Important racial/ethnic disparities in perioperative outcomes were observed among patients undergoing major cancer and noncancer surgical procedures at American College of Surgeons National Surgical Quality Improvement Program institutions. There were fewer disparities among individuals undergoing cancer surgery, though black patients, in particular, were more likely to experience prolonged length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(48 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…1 This relationship extends to the surgical domain where black patients were demonstrated to have a prolonged length of hospital stay in 10 of the 16 major procedures studied. 2 This study, however, failed to demonstrate a disparity in overall complication rates in cases of major urologic cancer surgery-radical cystectomy, radical prostatectomy, and nephrectomy. Previous publications have also been unable to define the contribution of differences in individual patient-level characteristics to any identified disparity between the race groups because these studies have generally used multivariable logistic regression analyses.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…1 This relationship extends to the surgical domain where black patients were demonstrated to have a prolonged length of hospital stay in 10 of the 16 major procedures studied. 2 This study, however, failed to demonstrate a disparity in overall complication rates in cases of major urologic cancer surgery-radical cystectomy, radical prostatectomy, and nephrectomy. Previous publications have also been unable to define the contribution of differences in individual patient-level characteristics to any identified disparity between the race groups because these studies have generally used multivariable logistic regression analyses.…”
Section: Introductionmentioning
confidence: 71%
“…Previous publications have also been unable to define the contribution of differences in individual patient-level characteristics to any identified disparity between the race groups because these studies have generally used multivariable logistic regression analyses. 2,3 Important biological differences in disease between black and white patients that impact complications also need to be factored in. Population-based data suggest that the incidence of prostate cancer and the rate of progression to distant disease is higher among black men.…”
Section: Introductionmentioning
confidence: 99%
“…Barriers in culture, language, and medical literacy may all play a role in this disparity in access, which is consistent with prior literature indicating racial differences in peri-operative outcomes. 23 Insurance provider also significantly influenced likelihood of receiving Delayed-CCY, as patients with Medicaid-insurance and no insurance were significantly less likely to have Delayed-CCY compared to patients with private insurance. Our data are consistent with prior literature suggesting uninsured and Medicaid patients undergo emergent repair of ventral hernias at a significantly higher rate than patients with private insurance, who typically undergo elective hernia repair.…”
Section: Discussionmentioning
confidence: 99%
“…Holding other covariates and outcome variables in the model constant, non-Hispanic White participants are expected to have 26% more days spent in the hospital as compared to non-Hispanic minority participants. Although health disparities research has identified racial differences in cancer treatment recommendations (Li, Malone, & Daling, 2003; Shavers & Brown, 2002) and choices (Hurwitz et al, 2016; Ross et al, 2016), research examining hospital length of stay has found non-White cancer patients have longer stays as compared to their White counterparts (Parsons, Habermann, Stain, Vickers, & Al-Refaie, 2012; Ravi et al, 2015). A potential explanation for our conflicting finding may be due to the heterogeneity of the cancer diagnoses of participants in this study.…”
Section: Discussionmentioning
confidence: 99%